Modification of Acylation and Succinylation of Tapioca Starch - Rini Hustiany; Dedi Fardiaz; Anton Apriyantono; Nun . (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2005)
Modified starch is one of ingredients commonly used in food processing for coating and flavor encapsulation. This component can be made by modifying the structure of native starch either through chemical or enzymatic reaction. This research was aimed to chemically modify tapioca starch into a modified starch with improved coating characteristic. The tapioca starch was first hydrolyzed to a hydrolyzate with dextrose equivalent of 9.1, Both tapioca starch and hydrolyzate were further acylated with stearic acid and propiooic acid and succinylated with succinic acid. The concentrations of acids used for acylation and succinylation were 2,44. 4.76 and 9.09%. The modified starches were analyzed for their yield and moisture content, the degree of substitution, functional groups, crystalline structure polarization, gelatinization properties and viscosity. The moisture content of the modified starches was 1.52-3.32% and the yield was 87.45-95.43%. The hydroxyl group substitution into acyl and succinyl groups was low, i.e 0.03-0.04 and 0.05-0.08 respectively. The result show that methyl. methylene and CO carbonyl groups were formed in the modified starches. The crystalline structure of the modified starches was broken. This revealed that the peak 22.620 was widen and the doublet were disappearing on peak 16.850 and 17.990 Birefringence of the acylated and succinylated starch changed significantly and disappeared in the case of acylated and succinytatod hydrolizate. The initial and optimum gelatinization temperature of acylated and succinylated starch were 57.6-64.200 and 68.62-9i4’C respectively, and the maximum viscosity was 14-714 Brabender Unit. No initial and optimum geletanization temperature nor maximum viscosity was found in acylated and succinylated hydrolyzate. Based on our finding it is suggested that acylation (9,09%) and succinylatim (4.76%) of tapioca starch can be used to modify the starch into a product with better coating characteristic.,br> Key words : tapioca starch, modified starch, hydrolyzed starch. acylation, succinylation